Manic episode following psilocybin use in a man with bipolar II disorder: a case report - Halim, Haniya J.; Burk, Bradley G.; Fargason, Rachel E.; Birur, Badari (Frontiers in Psychiatry, 2023)
There has been an increase in research on the topic of psychedelic substances and their effects as treatment options in neuropsychiatric conditions. Psilocybin is a psychedelic drug that has recently garnered increased interest as an effective treatment modality for treatment-resistant depression, depression associated with terminal conditions, certain substance use disorders, and obsessive-compulsive disorder. However, sparse data exist as to the effects that psilocybin might have on patients at risk for mania, in large part secondary to the exclusion of this patient population from studies due to the concern for inducing mania or worsening illness course. We describe a case of a 21-year-old male with a recent diagnosis of bipolar II disorder who developed a manic episode following the ingestion of psilocybin in the form of hallucinogenic mushrooms. Given the incidence of depression in those with bipolar disorder, impulsivity, and a tendency to abuse substances associated with the illness, further research is needed into the risks of psilocybin and other psychedelic use in those with bipolar disorder.